A comparative case study of the strategies used by grade one teachers who teach through the medium of English - Jackson, Gail (Rhodes University, Faculty of Education, Department of Education, 2004)
This research project begins by exploring the problems surrounding the implementation of the 1997 Language in Education Policy (LiEP), and offers insight into why some schools, despite the promotion of additive bilingualism, choose English as the primary medium of instruction. It is a comparative case study of two Grade 1 classes in different situational contexts, which highlights the teaching strategies and language practices of teachers who teach predominantly non-English speakers through the medium of English. Research carried out through this case study illustrates the use of a wide range of teaching strategies, which assist young learners when learning through an additional language. In School A, thematic linking between different learning areas to maximise vocabulary development in both the mother tongue and the additional language, as well as repetition, recycling, scaffolding and contextualisation of content were found to be important. In addition, the use of questioning to elicit understanding, as well as classroom organisation and code-switching were strategies which assisted both the teacher and learners in this multilingual environment. In School B, class size, group work and the inclusion into the timetable of a wide range of diverse activities over and above the main learning areas, which provided opportunities for language development, were important considerations. In addition, routine, predictability and an attention to detail, in keeping with a form-focussed approach, aided the children in understanding the mechanics of literacy and guiding them towards becoming phonologically aware.
Keywords: Native language and education -- South Africa; Language policy -- South Africa; Language and education -- South Africa; English language -- Study and teaching (Elementary) -- South Africa; Multilingualism -- South Africa; Education, Bilingual -- South Africa